Investment options for integrated water-livestock-crop production in Sub-Saharan Africa - Peden, Donald G.; Freeman, H.A.; Astatke, A.; Notenbaert, An Maria Omer (International Water Management Institute, 2005)
This paper focuses on enhancing returns on investments in agricultural water through effective integration of livestock production. It suggests that multi-sectoral approaches to investment in water, soil, crop and livestock will have greater development impact and profitability than developing water and livestock independently in the same areas.